2017
DOI: 10.1007/s00774-017-0849-0
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic calcification and the risk of bone fractures: a meta-analysis of prospective cohort studies

Abstract: The relationship between abdominal aortic calcification (AAC) and bone fracture has been examined by some observational studies, but the results remain discordant. Therefore, we aimed to assess the link between them by conducting a meta-analysis of prospective studies. Relevant studies were identified by searching PubMed and EMBASE databases until the end of December 2016. Summary relative risks (RRs) and 95% confidence intervals (CIs) for associations between AAC and fracture risk were estimated with fixed- o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In China, a prospective osteoporosis study followed 1,724 postmenopausal women for 5 years, they found the presence of aortic calci cations assessed using semiquantitative radiography at baseline was associated with a higher rate of vertebral fractures (12.2% vs. 4.5% in women with and without aortic calci cations, (P = 0.01) (28). This study was pooled in a further meta-analysis on the relationship of aortic calci cations to the risk of fracture, which demonstrated that aortic calci cations was signi cantly and independently associated with a higher fracture risk, recruiting 14,632 participants in total (27). For peripheral arterial disease (PAD), in a prospective study of 1,332 individuals, peripheral arterial disease (PAD) measured by ABI was not associated with the occurrence of fractures (29).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In China, a prospective osteoporosis study followed 1,724 postmenopausal women for 5 years, they found the presence of aortic calci cations assessed using semiquantitative radiography at baseline was associated with a higher rate of vertebral fractures (12.2% vs. 4.5% in women with and without aortic calci cations, (P = 0.01) (28). This study was pooled in a further meta-analysis on the relationship of aortic calci cations to the risk of fracture, which demonstrated that aortic calci cations was signi cantly and independently associated with a higher fracture risk, recruiting 14,632 participants in total (27). For peripheral arterial disease (PAD), in a prospective study of 1,332 individuals, peripheral arterial disease (PAD) measured by ABI was not associated with the occurrence of fractures (29).…”
Section: Discussionmentioning
confidence: 88%
“…Correlations between arterial stiffness and BMD have been frequently reported in both retrospective and cross-sectional studies. A cross-sectional study involving around four thousand Chinese men and women aged 65-92 reported that ankle brachial index (ABI) as a measurement for peripheral arteriosclerosis was positively correlated with hip BMDs (27). Further, prospective studies have also reported ndings in evaluating whether low BMD predicts cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between arterial stiffness and BMD have been frequently reported in both retrospective and cross-sectional studies. A cross-sectional study involving around four thousand Chinese men and women aged 65-92 reported that ankle-brachial index (ABI) as a measurement for peripheral arteriosclerosis was positively correlated with hip BMDs [38]. Further, prospective studies have also reported findings in evaluating whether low BMD predicts cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a significant univariate association between high Agatston score and 1-year incidence, and between high Agatston score and ≥ 2 incident VFs within 1 and 3 years, we did not find any significant multivariate associations between Agatston score and incident VFs after adjusting for age, sex, BA, and prevalent VFs. A recent meta-analysis examined data from prospective cohort studies of aortic calcification and fractures [41]. Although not all individual studies found significant results, it was reported that subjects in the high aortic calcification category had increased fracture risk compared to subjects in the zero category.…”
Section: Discussionmentioning
confidence: 99%